Self-Reported Population Health : an International Perspective Based on EQ-5D. - Szende, Agota. (Springer Netherlands, 2013)
The EQ-5D survey enables vital transnational comparisons to be made on self-assessed health. This volume has an unprecedented range of tabulated data from the 24 participating nations, and includes clear explanations as well as guidance for users.